The Directions of Development of Long-Term Care Services in Poland - Furmańska-Maruszak, Agnieszka; Wójtewicz , Anna (Studia Oeconomica Posnaniensia, 2016)
Formal long-term care in Poland is reserved for the most deprived and is divided between two systems: a system of social welfare and a health care system. Growing care needs in Polish society have created a discussion of a public-private funding model of care in which the criterion of public support would be based on the degree of dependence of an elderly person. The aim of the article is to analyze the current and planned solutions for long-term care and the manner of financing it in Poland.